AUDITORIA DE MARKETING NA EMPRESA JÉSSICA METDZDORF ATELIER - Pias, Angelica Hammel; Lacerda, Ana Carolina Stocker; Da Rosa, Geovana Caroline Dos Santos; Zimmermann, Jéssica Dos Santos; Milani, Júlia Da Silva; Lima, Larissa Girardi (Salão do Conhecimento, 2018)
Projeto de pesquisa no curso de Administração da Unijuí